Online Parenting Classes for the Interest of Midwifery Entrepreneurship Students - Anggraini, Dina Dewi; Sari, Marlynda Happy Nurmalita (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2023)
In order to foster entrepreneurial interest and prepare midwifery graduates to become job creators through entrepreneurship to create their own jobs, this can be done in the form of health service parenting education programs. This program can be given to parents wherever they are, not limited by distance and place. The implementation of the parenting education program is an online parenting classes. This activity was carried out to assess the effect of implementing online parenting classes on the entrepreneurial interest of midwifery students. The activity is pre-experimental by using one pretest group-posttest design. The number of samples is 10 midwifery students determined by purposive sampling. The intervention was carried out by establishing and implementing an online parenting classes program. Data collection was carried out through a questionnaire in the form of a Google form that was given before and after the intervention. Data analysis used the SPPS paired t-test. The result obtained is a p-value of 0.000 which means <0.05. From this it shows that there is an influence of implementing online parenting classes on the entrepreneurial interest of midwifery students.